Design to Resolve Case of Disqualification of Winning Candidates in Local Government Head Elections in Indonesia - Siboy, Ahmad; Al-Fatih, Sholahuddin; Jaelani, Abdul Kadir (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research is focused on investigating what does the relevant design of the resolution of disqualification of the winning candidate in an election look like. This research employed normative method, case, conceptual, and statutory approaches. The research result reveals that there are several alternatives that can be taken as measures: (i) criminal administrative violation brought to court following election votes cannot be processed and is deemed null and void from the outset; (ii) this violation and the disputes over the voting results are investigated by the Supreme Court and Specific Judicial Body (BPK) concurrently; (iii) the proposed design implies that the administrative violation should be tried by Supreme Court and when the Supreme Court disqualifies a winning candidate pair with the major votes, the Constitutional Court should no longer continue the case. On the contrary, when the trial initially takes place in the Constitutional Court, the administrative violation cannot be resolved unless the Constitutional Court rejects the case or declares it invalid.